The Effect of Oleic Acid-Grafted Linear Low-Density Polyethylene as Compatibilizer on the Properties of Linear Low-Density Polyethylene/Cyclic Natural Rubber Blends - Ahmad Hafizullah Ritonga; Novesar Jamarun; Syukri Arief; Hermansyah Aziz; Denny Akbar Tanjung; Boy Isfa (International Journal of Technology, 2023)
In this paper, we report that the compatibility of polymer blends between linear low-density polyethylene (LLDPE) and cyclic natural rubber (CNR) can be increased by the addition of oleic acid-grafted linear low-density polyethylene. The research aims to investigate the effect of LLDPE-g-OA compatibilizer in LLDPE/CNR blends on improving the mechanical properties and characteristics of the blends. The LLDPE/CNR/LLDPE-g-OA blends (compatible blends) were prepared by blending methods in the molten phase using an internal mixer set at a temperature of 160oC with a rotation speed of 100 rpm. The LLDPE pellets were inserted into it until melts and followed with an addition of CNR and LLDPE-g-OA. The tensile strength test results have shown an increase in mechanical properties after the addition of the compatibilizer with a maximum content of 4 wt%. The difference in FTIR spectra of compatible blends is indicated by the presence of C=C bonds from CNR, which appear at 1654.9 cm-1, indicating the occurrence of physical bonds in the blends. The existence of the LLDPE-g-OA compatibilizer has increased the thermal stability of the polymer blends and changes in the melting point temperature of 1240C. Compatible blends showed that the surface morphology was smoother, and there were significant microstructural changes compared to incompatible blends.